Avaliação ambiental e previsão dos resíduos da arborização urbana de João Pessoa como alternativa energética - Araújo, Yuri Rommel Vieira (2017)
Urban forest generates a significant amount of biomass solid waste. This dissertation carried out the environmental evaluation and the prediction of the residues coming from the urban forest of João Pessoa as an energetic alternative. More specifically, the objectives were: i) to diagnose and plan the maintenance of urban forest in Joao Pessoa; ii) to evaluate the environmental impacts and to analyze different scenarios for urban forest residues in João Pessoa, with a view to inclusion in the clean development mechanism (CDM), and iii) to analyze the forecast of the volume of residues coming from urban forest in João Pessoa. In catch up to achieve the objectives, the inventory of urban afforestation was carried out by means of simple random sampling, a Life Cycle Assessment (LCA) was developed with the IPCC 2013 GWP 100a method, and models of the ARIMA Family (Autoregressive Integrated Moving Average). It was verified that the urban forest is distributed irregularly by the municipality, being outstanding in abundance the species F. benjamina, S. siamea and T. catappa and with the highest indexes with phytopathological problems, physical damage and conflicts with equipment Urban. The environmental assessment showed that the current disposal (landfill) is the most impactful for the environment; The best scenario was the generation of electricity, including the possibility of being used as carbon credits. The application of the ARIMA model (0,1,4) provided a better prediction for the 12 periods of the volume of residues of the urban forest of João Pessoa.